The personal history, adventures, experience & observation of David Copperfield : the younger, of Blunderstone Rookery : which he never meant to be published on any account - Dickens, Charles, 1812-1870. (New York : Modern Library, 1950)
David Copperfield is the story of a young man's adventures on his journey from an unhappy & impoverished childhood to the discovery of his vocation as a successful novelist. Among the gloriously vivid cast of characters he encounters are his tyrannical stepfather, Mr Murdstone; his formidable aunt, Betsey Trotwood; the eternally humble yet treacherous Uriah Heep; frivolous, enchanting Dora; & the magnificently impecunious Micawber, one of literature's great comic creations. In David Copperfield--the novel he described as his 2favorite child3{u2014}Dickens drew revealingly on his own experiences to create one of his most exuberant & enduringly popular works, filled with tragedy & comedy in equal measure.
Steerforth's home -- Little Em'ly -- Some old scenes, and some new people -- I corroborate Mr. Dick, and choose a profession -- My first dissipation -- Good and bad angels -- I fall into captivity -- Tommy Traddles -- Mr. Micawber's gauntlet -- I visit Steerforth at his home, again -- A Loss -- A Greater loss -- The Beginning of a long journey -- Blissful -- My aunt astonishes me -- Depression -- Enthusiasm -- A Little cold water -- A Dissolution of partnership -- Wickfield and Heep -- The Wanderer -- Dora's aunts -- Mischief -- Another retrospect -- Our housekeeping -- Mr. Dick fulfils my aunt's predictions -- Intelligence -- Martha -- Domestic -- I am involved in mystery -- Mr. Peggotty's dream comes true -- The Beginning of a longer journey -- I assist at an explosion -- Another retrospect -- Mr. Micawber's transactions -- Tempest -- The New wound, and the old -- The Emigrants -- Absence -- Return -- Agnes -- I am shown two interesting penitents -- A Light shines on my way -- A Visitor -- A Last retrospect.
Includes bibliographical references (page xiii).
Keywords: 1800-1899; Child labor -- England -- London -- Fiction; Young men -- England -- Fiction; Orphans -- England -- Fiction; Enfants -- Travail -- Angleterre -- Londres -- Romans, nouvelles, etc; Manners and customs; England -- Social life and customs -- 19th century -- Fiction; English fiction; Autobiographical fiction; Fiction; Autobiographical fiction